2021
DOI: 10.1002/anie.202014551
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Manganese Oxide Intermediates in Electrochemical Water Oxidation at Neutral pH by In Situ Raman Spectroscopy

Abstract: Electrochemical water splitting is a promising means to produce eco‐friendly hydrogen fuels. Inspired by the Mn4CaO5 cluster in nature, substantial works have been performed to develop efficient manganese (Mn)‐based heterogeneous catalysts. Despite improvements in catalytic activity, the underlying mechanism of the oxygen evolution reaction (OER) is not completely elucidated owing to the lack of direct spectroscopic evidence for the active Mn‐oxo moieties. We identify water oxidation intermediates on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 88 publications
3
30
0
Order By: Relevance
“…As shown in Figure d, the powder X-ray diffraction (XRD) spectrum of our NPs well match with the Mn 3 O 4 phase (PDF#: 00-024-0734). In addition, the spectra of the Raman spectroscopy analysis clearly demonstrate the characteristic Raman bands of spinel Mn 3 O 4 (hausmannite) at the peak position of 290, 320, 373, 479, and 659 cm –1 (Figure e). , The peak position of both Mn 2p 3/2 and Mn 2p 1/2 peaks are located at 641.57 and 653.5 eV (Figure f), which matches well with previous studies of Mn 3 O 4 . , …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure d, the powder X-ray diffraction (XRD) spectrum of our NPs well match with the Mn 3 O 4 phase (PDF#: 00-024-0734). In addition, the spectra of the Raman spectroscopy analysis clearly demonstrate the characteristic Raman bands of spinel Mn 3 O 4 (hausmannite) at the peak position of 290, 320, 373, 479, and 659 cm –1 (Figure e). , The peak position of both Mn 2p 3/2 and Mn 2p 1/2 peaks are located at 641.57 and 653.5 eV (Figure f), which matches well with previous studies of Mn 3 O 4 . , …”
Section: Resultssupporting
confidence: 89%
“…We have previously developed sub-10 nm-sized manganese oxide nanocatalysts, which exhibited good OER activity under neutral conditions. , Combined with in situ spectroscopic analysis (X-ray absorption, UV–vis, and Raman spectroscopy) and electrokinetic studies, we revealed their unique reaction mechanism which was totally different from that of the bulk crystalline manganese oxide electrocatalysts . The RDS is the chemical O–O bond formation where Mn­(IV)O species are involved in ref . It was indicated that the charge accumulation process was facilitated via an Mn valence change prior to the O–O bond formation step.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the GaN:Mn samples, the appearance of mode D was observed. It resembled mixed structures observed in Mn 3 O 4 by Cho et al [ 34 ], who investigated the influence of the Mn oxidation state on the Raman spectrum. In GaN doped with Mn, Mn was present in the neutral state with the acceptor level pinned at 1.8 eV above the vbm [ 25 ].…”
Section: Discussionsupporting
confidence: 69%
“…Using this explanation mode, E can be related to the presence of Mn–C 2 cation complexes. The origin of the last peak, pinned at 770 cm −1 , was the state [ 34 ]. The described spectra showed that for the co-doped samples, C and Mn interacted with each other.…”
Section: Discussionmentioning
confidence: 99%
“…[ 82–84 ] In recent decades, the rapid development of in situ Raman technique realizes its wide applications in the fields of catalysis. [ 85 ] In OER, in situ Raman spectroscopy has been widely used to determine the surface structural evolution which is highly potential‐dependent ( Figure 6 a). [ 86 ] For example, Chen and co‐workers have probed the gradual phase transformation from NiCeO x H y to γ‐NiOOH via performing the in situ Raman spectroscopy, as indicated by the emerging Raman peaks at 474 and 554 cm −1 .…”
Section: Other Characterizationsmentioning
confidence: 99%